Життєвий шлях і наукова спадщина В. А. Богусевича - Абашина, Н.С. (Археологія і давня історія України, 2022)
У статті розглядається наукова біографія відомого археолога, історика і музейника, дослідника
пам’яток Київської Русі Володимира Андрійовича
Богусевича (1902—1978 рр.). Провідне місце у його
науковому доробку посідають проблеми походження і формування давньоруських міст, їх топографії
і соціальної структури, будівництва середньовічних оборонних споруд. In July 24, 2022 is the 120th anniversary of the famous
archaeologist, historian and museologist, the
researcher of archaeological sites of Kievan Rus, Candidate
of Historical Sciences Volodymyr Andriyovych
Bogusevych (1902—1978).
V. A. Bogusevich graduated from the historical
and economic department of Leningrad Herzen State
Pedagogical Institute (1925) and postgraduate studies
at the State Academy of the History of Material Culture
(1929). In 1929—1931 he was a research officer at
the State Academy of the History of Material Culture;
in 1931—1935 — the Deputy Director for Research
and Scientific Secretary of the Pskov State Museum;
1935—1941 — the Deputy Director for Science of the
Administration of the Novgorod State Museums and
Senior Research Fellow of the Novgorod Section of the
Institute of History of the USSR Academy of Sciences;
1945—1946 — the Deputy Director for the scientific
part of the State Historical and Cultural Reserve «Kyiv-
Pechersk Lavra»; 1947—1962 — the Senior Research
Fellow, Head of the Department of Slavic Archeology of
the Institute of Archaeology of Academy of Sciences of
Ukrainian SSR. In 1947 Bogusevich received his Candidate
of Sciences degree.
He studied the archeological sites of Novgorod
(1937—1941), Kyiv (1948, 1950—1952, 1957), Chernihiv
(1947—1949, 1951, 1953), the Rus cities of Voin
(1956—1957), Gorodets Ostersky (1954, 1961), Vyr
(1958—1959), V’yahan (1959), Putivl (1960—1961),
settlements of the Slavs near Kaniv (1947—1948).
V. A. Bogusevych’s contribution to the archeology
of Kyiv is significant. He supervised the dismantling
of the ruins of the Assumption Cathedral of the Kyiv-
Pechersk Lavra (1945—1948), explored the archeological
sites of the Kyiv-Pechersk Lavra and the Upper
Town, conducted the first excavations in Podil, discovered
the wall of the «city of Yaroslav».
The excavations of V. A. Bogusevych on the territory
of the Chernihiv Kremlin and on the Tretyak were
the beginning of the study of ancient parts of the city.
This allowed him to develop the historical topography
of Chernihiv.
V. A. Bogusevich is the author of more than 60 scientific
and popular works. In research he made extensive
use of written sources supplementing them with archaeological
material. V. A. Bogusevych’s works demonstrate
a concrete-historical approach to the problems
of the origin and formation of the cities of Kievan Rus,
their topography and social structure, the construction
of medieval fortifications.